Industrial training report: Majlis Bandaraya Ipoh / Nur Aina Nadhirah Mohamed Azman - Mohamed Azman, Nur Aina Nadhirah (Universiti Teknologi MARA, Perlis, 2023)
As an ordinary student, entering the world of employment is something that very unfamiliar as this new phase are quite challenging to be adapt of since some individuals have been never experience jobs life. This internship programme report emphasises the author's most significant contributions from both academic and non-academic angles. This document's purpose is to identify and summarise the analysis done, the projects finished, the experience obtained, and the accomplishment as an intern. To finish her internship, the author was transferred to Majlis Bandaraya Ipoh (MBI). By having the opportunity to work in the atmosphere that MBI provided and learning about some new words, technologies, and languages, the author considered herself to be pretty lucky. Amazingly, working in a multicultural workplace was the finest experience. Although there are racial differences among the management staff, the author is able to identify how they work together successfully finishing their job. Since the author experienced changing in units under the department every few months, this project she worked on undoubtedly helped her expose herself to a wider part of practical knowledge, which was very helpful in improving her views regarding different usage of management frameworks in every department. In addition to the system utilisation, there were a few other difficulties. Some of them were technical while others weren't. As her internship concludes, the author realises that some of her management and communication abilities have improved as a result of being required to undertake customer service-related front-line tasks. As a result, she has learned how to handle job now and in the future with greater assurance, expertise, and professionalism.